Understanding the societal dilemma of genetically modified food consumption: a stimulus-organism-response investigation - Hui, Xu; Amponsah, Randy Kwaku; Antwi, Samuel; Gbolonyo, Patrick Kweku; Ameyaw, Moses Agyemang; Bentum-Micah, Geoffrey; Adjei, Edward Oppong (Frontiers in Sustainable Food Systems, 2024)
Consumer worries about their health and the environment are drawing attention to the usage of genetically modified food on a global scale. The study aims to provide fresh insight into how consumers view GM foods and how they plan to respond to them. Data were collected from Chinese consumers, who are at the advanced stage of GM food, and Ghanaians, who are at the early stage of GM food. The data were analyzed using Smart PLS, R-Studio, and SPSS. Based on a valid response from nine hundred and seventy-six (976) respondents across the two countries, the results demonstrate the dynamics of GM acceptance among consumers and provide valuable insights for policymakers and businesses in the GM foods industry. Our research adds up to the relatively fewer studies which have addressed GM food consumption likelihood from consumers across different stage of GM food readiness.